Synthesis of Fluorine Containing Tetracyclic Ring Systems: 1,2,4-triazino [3’,4’,3,4] [1,2,4] triazino [5,6-b] Indole and 1,2-4-triazino [4’,3’:2,3] [1,2,4] triazino [5,6-b] Indole - Dandia, Anshu; Ahmed, Nidhal; Sehgal, Varinder; Saha, Mitali (Asian Journal of Chemistry, 2010)
Tetracyclic ring systems viz. 2-methyl-1-oxo-11H-1,2,4-triazino [3´,4´:3,4][1,2,4] triazino [5,6-b] indole (V) and 3-methyl-4-oxo-11H- 1,2,4-triazino [4´,3´:2,3] [1,2,4] triazino [5,6-b] indole (VI) were synthesized by the cyclization of 2-oxo-propionic acid [5H- 1,2,4-triazino] [5,6-b] indole-3-yl hydroazone (IV). Cyclization of (IVb) (X = 7-F) and (IVc) (X = 8-F) afforded the angular product (V) exclusively, while cyclization of IVa (no F) and IVd (X = 9-CF3) gave a mixture of angular (V) and linear products (VI) in the ratio 3 : 1. Compound (IV) was prepared from III on heating with sodium hydroxide in ethanol-water (50 : 50) while the hydrazide (III) was itself obtained by the condensation of 3-hydrazino dervatives (II) with ethyl pyruvate in absolute ethanol. The synthesised compounds may prove to be effective pesticides also.